De novo mitral regurgitation as a cause of heart failure exacerbation in patients with hypertrophic cardiomyopathy. (1st February 2018) - Kuperstein, Rafael; Klempfner, Robert; Ofek, Efrat; Maor, Elad; Freimark, Dov; Sternik, Leonid; Goldenberg, Ilan; Raanani, Ehud; Arad, Michael
Abstract: Aims: To determine the prevalence and mechanisms of de novo severe MR due to mitral valve structural abnormalities causing clinical deterioration in patients with HCM. Methods and results: This is an observational study based on HCM registry comprising consecutive HCM patients ( n  = 397) who have been evaluated and followed in the Cardiomyopathy Clinic of Sheba Medical Center. Sixteen patients (4.0%), 8 males, mean age 65 ± 14 years, developed acute clinical deterioration due to development of severe mitral regurgitation unrelated to mitral valve systolic anterior motion. Compared to the remaining HCM population, those patients were older at their initial diagnosis (51 ± 20 vs. 38 ± 18 years) and more often females. Most frequently (in 10 patients, 63%) mitral regurgitation resulted from a flail posterior leaflet, while 4 patients had severe prolapse and 2 had isolated mitral annular/leaflet calcifications. Fourteen underwent surgery; myxomatous changes were found in all excised valves ( n  = 9). On age-adjusted univariate analysis, 3 clinical parameters remained significantly associated with the development of de novo MR, female gender, LVOT obstruction and significant MR at baseline. On multivariable analysis, only LVOT obstruction (HR = 3.8) and MR at baseline evaluation (HR = 8.2) predicted development of severe MR. Conclusions: De novo severe MR leading to acute heart failure was repeatedly observed in our HCM series. This etiology needs to be considered as a cause of acute clinical deterioration in these patients. Highlights: We describe a series of patients with HCM who were clinically stable who presented with acute heart failure symptoms. All patients underwent a trans-esophageal echocardiogram. De novo severe mitral regurgitation was found in 4% of these patients.